Survey on social networking services. Issue 4 (1st December 2013) - Irfan, Rizwana; Bickler, Gage; Khan, Samee U.; Kolodziej, Joanna; Li, Hongxiang; Chen, Dan; Wang, Lizhe; Hayat, Khizar; Madani, Sajjad Ahmad; Nazir, Babar; Khan, Imran A.; Ranjan, Rajiv
Abstract : The social computing, such as social networking services (SNSs) and social Networking Platforms (SNPs) provide a coherent medium through which people can be interactive and socialize. The SNP is a Web‐based social space, specifically designed for end user‐driven applications that facilitate communication, collaboration and sharing of the knowledge through a variety of SNSs, such as text, video and audio streams. In the conventional SNPs, such as Facebook, LinkedIn and MySpace, computers are not capable of acquiring the information based on the common intelligence and human behaviour. This survey provides a comprehensive overview of the current SNSs and discusses different possibilities of incorporating the existing SNSs into the context‐aware techniques that include semantic Web, social search and social recommendations. The context‐aware computing provides services customisation based on the individual human characteristics, such as human preferences, mood, behaviours, and emotions. The Integration of contextual information with SNSs can be more useful and productive for the development of the intelligent social communicational services. This survey provides several possible future research directions especially in the field of social search and recommendation that can provide better social communication capabilities. Moreover, this study will provide new directions to the future researcher for designing future generation context‐based SNSs that provide services based on the on‐demand collaboration.